New aesthetic and the meaning of culture in the Caribbean : 'The Dream Coming in with the Rain' : proceedings - Springer, Pearl Eintou ed. (CARIFESTA VI Secretariat Port of SpainTT, 1995)
Looks at the origins of CARIFESTA, its historical background and current role in helping to develop and shape a Caribbean cultural identity. Examines the roots of Caribbean cultural identity and the aesthestics, culture and the religion in the Caribbean. Deals with the tasks facing this region in the task of creating 'cultural icons and new art forms' which truly speak of our cultural identity.